Streets, Bedrooms, and Patios : The Ordinariness of Diversity in Urban Oaxaca - Higgins, Michael James; Coen, Tanya L. (Tanya Leigh) (Book collections on Project MUSE., 2000)
In this rich ethnography of Oaxaca, Mexico, the authors look at the lives of people that are often marginalized: the urban poor, transvestite and female prostitutes, discapacitados (the physically challenged), gays and lesbians, and artists and intellectuals